HARMONICS FROM NON-LINEAR LOAD - CHE HUSSIN, AHMAD HAFIZ (IRC, 2014)
In these modern day, to maintain the sinusoidal waveform in the system had become a challenge to the electrical engineers when there a present of waveform distortion know as harmonics. The usage of non-linear in the system is the contribution of the harmonic present in the system. Harmonic is not a new thing but problem occur to the system caused by harmonic detected in the past few years. Harmonics component in an AC power system is defined as a sinusoidal component of periodic waveform that has a frequency equal to an integer multiple of the fundamental frequency of system (50Hz). Most of the load in these modern day full with electronic component especially solid state component that produce harmonic and they can varies from load to load. The increasing of current harmonic in the system that exceeded the limit stated by IEEE 519 standard will affect the system voltage and lead to problem in the system performance such as overheating problem, failure of insulation, failure of control system and affect the behavior of protection device that connected in the system. Harmonic is not a problem until they had exceeded the standard limit.